Pengaruh Konflik Peran dan Lingkungan Kerja terhadap Kinerja Karyawan pada Bank Bengkulu Cabang Pembantu Mega Mall - Noviansyah Noviansyah; Ahmad Soleh; Mimi Kurnia Nengsih (UNIVED Press, 2022)
The purpose of this study was to determine the effect of role conflict on employee performance and to determine the effect of work environment on employee performance. The population and sample in this study amounted to 11 people. The data analysis technique used in this study is multiple regression analysis, determination test and hypothesis testing. Data collection methods used were observation, interviews, questionnaires. The results of the regression analysis showed Y = 42,444 -0,146X1 + 0,141 X2. Based on the results of hypothesis testing partially shows that role conflict has a negative and significant effect on employee performance. Meanwhile, the work environment has a positive and significant effect on employee performance.